The Effect of Financial Literacy and Investment Motivation on Investment Interest - Gultom, Parapat; Wulandari, Annisa; Rahmadhina, Namira Mudrikah (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
One of the challenges of the millennial generation in investing is the lack of knowledge about investment, because most of the millennial generation currently invest because of Fear of Missing Out (FOMO) not because they have their own motivation to invest. The aim of this research is to determine the influence of financial literacy and investment motivation on investment interest based on generational groups. The population in this paper is the Panca Budi Foundation academic community. This research uses a quantitative approach, with a sampling technique using a probability sampling method with a simple random sampling type. The number of samples in this research is 50. The type of data in this research is primary data obtained through questionnaires and secondary data obtained from journals and the official website of the Financial Services Authority and the Indonesian Stock Exchange. Based on data analysis and discussion, it can be concluded that financial literacy has a significant influence on investment interest, investment motivation does not have a significant influence on investment interest, generational groups do not moderate financial literacy but generational groups moderate investment motivation.